Plasma dynamic synthesis of ultradispersed zinc oxide and sintering ceramics on its basis by SPS method; Journal of Physics: Conference Series; Vol. 830 : Energy Fluxes and Radiation Effects 2016 - Shanenkova Yu. L. Yuliya Leonidovna; Sivkov A. A. Aleksandr Anatolyevich; Ivashutenko A. S. Alexander Sergeevich; Shanenkov I. I. Ivan Igorevich; Firsov K. (Modification of materials with particle beams and plasma flows, 2017)
Title screen